Theoretical substantiation of the structural and functional model of forming future mathematics and physics teachers’ instrumental competences in the process of professional training - Broslavska, G. M. (Problems of Engineer-Pedagogical Education, 2018)
The author's structural and functional model of forming future mathematics and physics teachers’ instrumental competences in the process of professional training education is offered in the article. Based on the analysis of scientific and methodological works of domestic scientists and the conducted survey of respondents, it is determined that the structural and functional model of forming future mathematics and physics teachers’ instrumental competences in the process of professional training includes three interrelated blocks such as methodological-purposeful (social order, tasks, methodological approaches, principles, functions of forming future mathematics and physics teachers’ instrumental competences), content-actionable (components of the structures of forming future mathematics and physics teachers’ instrumental competences in the process of professional training, the object, subjects, methods, forms, means and periods of the formation of future mathematics and physics teachers’ instrumental competences in the process of professional training) and resulting (criteria, indicators and levels of the formation of future mathematics and physics teachers’ instrumental competences in the process of professional training and diagnostic tools for determining the effectiveness of the acquisition of these competences). The author explains that the result of the interaction of these blocks of the structural and functional model is the achievement of the goal, namely: future mathematics and physics teachers’ instrumental competences are formed in the process of professional training.